Study of Local Potential of MSMEs in Pelaga Village in Supporting The Achievement of A Sustainable Economy Based on SDGs - Sari, Retno Juwita (Institut Pariwisata Trisakti, 2025)
Pelaga Village has rich natural and cultural resources that can support sustainable economic development based on local wisdom. The village's strengths lie in its agriculture, plantations, and ecotourism sectors, with superior products like herbal coffee and asparagus offering broad market potential, both locally and internationally. This study aims to pinpoint the local potential of MSMEs as well as to improve their sustainability, inclusivity, and competitiveness. This study use qualitative research approach, utilizing depth interviews and parcipatory observation as the primary data collection method. This result of this research are to emphasize its tourism potential, while the MSMEs aspect based on local potential has not been explored in depth. This study examines MSMEs based on local potential in Pelaga Village not only as business units but also as instruments for driving a sustainable economy. By leveraging ecotourism potential, Pelaga Village can sustainably improve community welfare through the development of the agricultural sector and locally-based creative industries. Keywords: MSMEs, local potential, sustainable economy, SDGs, Pelaga village